2022
DOI: 10.1515/nleng-2022-0241
|View full text |Cite
|
Sign up to set email alerts
|

Mobile app for COVID-19 patient education – Development process using the analysis, design, development, implementation, and evaluation models

Abstract: There are many factors that can lead to the transmission of coronavirus disease 2019 (COVID-19), one of which is the lack of knowledge on the virus and its prevention, notably in Indonesia. This study was focused to design and build an interactive learning app for COVID-19 education. The design of this study was research and development, and in terms of the app development, it utilized the analysis, design, development, implementation, and evaluation model. The project was carried out from July to December 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…It could be concluded that the app could be used as a learning medium for patient education. Further studies, however, were needed to prove its effectiveness in the real clinical world [ 11 ]. Zare et al (2023), in study concluded The designed app was given to 20 people including nutritionists and parents with children under 18 years of age for conducting usability evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…It could be concluded that the app could be used as a learning medium for patient education. Further studies, however, were needed to prove its effectiveness in the real clinical world [ 11 ]. Zare et al (2023), in study concluded The designed app was given to 20 people including nutritionists and parents with children under 18 years of age for conducting usability evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Findings reflected a wealth of affordances in using technology characterized by learner satisfaction and productivity as well as organizational efficiency and satisfaction. Most notably, the technologies were pleasant to use, versatile, convenient and easily accessible for transferring knowledge to learners (namely, Ghozali, 2022). Figure 8 reflects the usability axial codes, and Appendix 7 provides a description of each code and an example from the studies included.…”
Section: Question 4 How Did the Use Of Technology Benefit The Develop...mentioning
confidence: 99%
“…The study used a convenience sample methodology and was conducted in the Special Region of Yogyakarta from January to February 2021. Individuals should meet certain eligibility criteria to participate, including being between the ages of 19 and 34 years old, being unvaccinated, having a mobile phone (speci cally Android OS), expressing a willingness to install the EduCovid-19® mobile phone app [15], and granting the agreement to participate in the study. A public notice requesting possible responders was distributed over two weeks via several social media sites, including WhatsApp, Facebook, and Instagram.…”
Section: Demographics and Sample Selectionmentioning
confidence: 99%